(untitled) (Forum Agribisnis, 2026)
Lemeu Pit Village is located in the vicinity of Kerinci Seblat National Park (TNKS), Lebong Regency, which has agroecological conditions that allow rice fields to be planted only once a year. Therefore, to support and stabilize farmers’ household income, when rice cannot be planted, the rice fields are converted for fish and duck farming. This activity is considered capable of increasing the efficiency of resource utilization and farmers’ income. This study aims to analyze the contribution of duck farming, identify internal and external factors of duck farming, analyze development strategies, and determine priority strategies for the development of duck farming in an integrated agricultural system in Lemeu Pit Village, Lebong Regency. The study was conducted in November 2025 using primary and secondary data. The analysis methods used included qualitative descriptive analysis, income contribution analysis, SWOT analysis, and QSPM analysis. The results showed that duck and fish farming contributed 25% and 16% as supplementary income, while rice contributed 59% as the main income in the integrated farming system. As a supplementary income source, duck farming in the SWOT analysis shows an internal factor value of 3,39 and an external factor value of 3,28, resulting in coordinates (1,36; 1,20) in quadrant I and producing four SO (Strengths-Opportunities) alternatif strategies, with the priority strategy being to increase the duck population through BUMDes credit capital support, with the highest Total Attractiveness Score (TAS) of 6,00. This strategy is expected to increase production, income, and the sustainability of duck farming in an integrated agricultural system. The implementation of this strategy must be supported by improvements in livestock management, particularly through more appropriate intensive rearing systems, increased farmer knowledge of alternatif feeds, and reduced disease incidence that could lower livestock productivity.